Pengaruh Pemahaman dan Sanksi Perpajakan terhadap Kepatuhan Wajib Pajak dengan Preferensi Risiko sebagai Variabel Moderasi - Retno Wulandari (STIE Perbanas Surabaya, 2020)
The purpose of this study was to examine the effect ( and to analyze) the understanding variable and tax penalties on tax compliance with risk preference as a moderating variable in taxpayers registered at KPP North Malang regenc. The data were collected using a questionnaire distributed to taxpayers selected based on a purposive sampling approach. They were analyzed by means of multiple linear regression analysis and moderating analysis using absolute difference value test approach. It was found that understanding and sanctions affect taxpayer compliance. Risk preference is also able to moderate understanding and tax sanctions on taxpayer compliance.